Analisis Pembelajaran di Luar Kelas dalam Materi Penjumlahan Menggunakan Pendekatan Realistic Mathematics Education (RME) pada Peserta Didik Kelas II SDN 1 Kebak Tahun Ajaran 2021/2022 - Ambarwati Ambarwati; Siti Supeni; Ema Butsi Prihastari (Departement of Mathematics Education, 2023)
This research was conducted at SDN 1 Kebak, Kebakkramat, Karanganyar in the 2021/2022 academic year with qualitative descriptive research. Data collection methods were through observation, interview, and documentation. Observations were made to obtain result regarding school profiles, facilities and infrastructure used in the learing process using RME interview were conducted to obtain information. The interview condudted in this study were structured interviews. In this study, the subjects were students in class 2 at SDN 1 Kebak in the 2021/2022 academic year. The validity used was source triangulation technique and technique triangulation. Meanwhile, to analize the data was through descriptive qualitative with the steps of data collection, data reduction, data display, and drawing conclusions. Based on the results of the research, it could be seen that the implementation of learning outside the classroom on addition material using the RME approach has been carried out at SDN 1 Kebak in the 2021/2022 academic year. There were 2 factors, including supporting factors which included internal factors and external factors, while inhibiting factors included 1) limited media in the surrounding environment, and 2) students who were not fluent in arithmetic. The solution made by the teacher to overcome this problem was use the RME approach: 1) found the right time so that learing could be done outside the classroom, 2) as much as possible made the use of the media in the surrounding environment, 3) asked and made sure students about things that were not clear and they did not understand. The teacher also provided motivation to students so that they were passionate about learning.